An Experimental Study on Tracking Identity of Moving Shapes: Do Stimulus Complexity and Familiarity Affect Tracking Accuracy of Male and Female Students? - Shuyang Zhang; Hashvini B. Kaliselvan; Tong Zhang; Aini Marina Ma'rof (Jurnal VARIDIKA, 2021)
The current study explored the effects of stimulus complexity and familiarity on tracking accuracy between male and female postgraduate students in Malaysia. Since online courses are not restricted by location, the convenience of recording classes has become a steady trend, especially during the COVID-19 period. However, some are also skeptical about the efficacy of online teaching and learning through the digital environment and believe that the stimulus generated on these foundations will result in undesirable consequences (Dhawan, 2020). As student attention determines their tracking accuracy, external factors like stimulus complexity and familiarity tend to be an obstacle for students to be attentive.  In this quantitative experimental study named "Simon Effect", 24 postgraduate students (12 males and 12 females) in a Malaysian public research university were used as samples to test whether or not gender plays a role in tracking accuracy. Results show that gender does not influence the tracking accuracy of postgraduate students. At the same time, the stimulus complexity and familiarity do influence the tracking accuracy of the postgraduate students. The implication of the study lies in promoting the teaching and learning sessions not only for a postgraduate student but for all the students in different educational levels during the COVID-19 period and maximizing the educational outcomes.